DNA Fingerprinting of Indian Potato Cultivars based on Inter Simple Sequence Repeats (ISSRs) - Dr, Vanishress G (Potato Journal, 2016)
Commercial scale fingerprinting of potato cultivars is made difficult by the need for speed, reliability and the ability to distinguish between large numbers of genotypes. In the present study the potentiality of ISSR-PCR for fingerprinting was evaluated using 11 multi loci ISSR markers on 47 commercial Indian potato cultivars. The complex band profiles generated were highly reproducible. A total of 68 distinct alleles were obtained with number varying from 3 (ISSR UBC079) to 9 (ISSR 827). The average fragments per (AM) marker and per genotype (AG) were 6.1 and 1.43 respectively with a total of 47 polymorphic fragments. Rp value varied from 4.17 (ISSR UBC079) to 12.26 (ISSRHB-10). The average RP was 7.60 per ISSR primer. The dendrogram analysis showed that Indian potato cultivars placed into three broad clusters which were in concordance with the Principle Component (PCO) analysis. Similarity coefficient varied from 0.82 to as high as 0.98 and PIC value of the markers ranged from 0.16 (ISSR UBC079) to 0.35 (ISSR 7). ISSR 827 and ISSR ACAa were able to distinguish maximum cultivars 21 and 10 respectively. But, no single primer was sufficient to distinguish all the cultivars. Furthermore, use of these markers in combination need to be checked for distinguishing all cultivars. The study revealed that ISSR-PCR technique seems to have potential for the large-scale and systematic fingerprinting of potato cultivars with added number of ISSR markers and high resolving techniques to unearth the diversity present in the Indian potato cultivars